Influence of Ecological Factors on the Production of Active Substances in the Anti-Cancer Plant Sinopodophyllum hexandrum (Royle) T.S. Ying - Liu, Wei (PLoS One, 2015)
The quality of traditional Chinese herbal medicine, which plays a very important role in the health system of China, is determined by the active substances produced by the plants. The type, content, and proportion of these substances may vary depending on ecological factors in areas where the plants are grown. Sinopodophyllum hexandrum (Royle) T.S. Ying, an endangered plant species with great medical value, was investigated in eight production locations representative of its natural geographical distribution range in China. The correlation between the contents of the active ingredients extracted from the roots and rhizomes of S. hexandrum and the ecological factors were evaluated step-by-step using a series of computational biology methodologies. The results showed that ecological factors had significant effects on the contents but not on the types of the active ingredients in eight production locations. The primary ecological factors influencing the active substances included the annual average precipitation, July mean temperature, frost-free period, sunshine duration, soil pH, soil organic matter, and rapidly available potassium in the soil. The annual average precipitation was the most important determinant factor and was significantly and negatively correlated with the active ingredient contents (P < 0.001). In contrast, organic matter was the most important limiting factor and was significantly and positively correlated with the active substances. These ecological factors caused 98.13% of the total geographical variation of the active ingredient contents. The climate factors contributed more to the active ingredient contents than did the soil factors. It was concluded that from the view of the contents of the secondary metabolites and ecological factors of each growing location, in Jingyuan, Ningxia Province, and Yongdeng, Gansu Province, conditions were favorable to the production of podophyllotoxin and lignans, whereas in Shangri-La, Yunnan Province, and Nyingchi, Tibet, conditions were favorable to the production of quercetin and kaempferol.